Training in a comprehensive everyday-like virtual reality environment compared to computerized cognitive training for patients with depression. (February 2018) - Dehn, Lorenz B.; Kater, Leona; Piefke, Martina; Botsch, Mario; Driessen, Martin; Beblo, T.
Abstract: Neurocognitive impairments in patients with depression compromise everyday functioning. Thus, should neuropsychological therapy be designed as real-life-like as possible to maximize transfer effects? We investigated whether ecological validity of computerized cognitive training could be increased by a comprehensive everyday-life-simulating training device combining virtual reality, 360°-all-around visibility and autonomous navigation motions. In an eight days training program, patients exercised the learning and purchasing of shopping list products in a virtual supermarket using either the novel training device (n = 21) or a corresponding desktop application (n = 17). In a pre-post-design, effects of the two training conditions were compared regarding several outcome measures. Altogether, results did not prove a benefit of the more naturalistic training setting regarding different training performances (recognition, performance speed, spatial orientation), self-perceived daily cognitive impairments, a real-life shopping task as well as various neuropsychological capabilities. Findings are discussed in the context of general challenges in striving after ecological validity in neuropsychology. Highlights: A novel real-life-like VR cognitive training for depressed patients was evaluated. Transfer effects were assessed by diverse cognitive and functional measures. There was no benefit of the naturalistic VR-setting compared to a PC-desktop setup. Exploratory analyses indicated small condition-dependent cognitive improvements.